Relationship between Soil-Transmitted Helminths Infection and Insulin Sensitivity in Adults at Padang City - Sitti Monica Astrilia Ambon; Nuzulia Irawati; Almurdi Almurdi (Journal of Agromedicine and Medical Sciences, 2021)
Helminth infections in Indonesia are most often caused by Soil-transmitted Helminths (STH) species. It turns out that STH infection has a protective effect against metabolic diseases by affecting glucose metabolism and insulin sensitivity. The effect related to the immune response that caused by STH infection. The aim of this study was to investigate the relationship between STH infection with insulin sensitivity in adults at Padang City. This study design was a comparative cross-sectional study with multistage random sampling technique. Stool samples were taken from 127 adults and there were 24 subjects (18.9%) infected with STH. Furthermore, We took another 24 uninfected subjects and compared their fasting blood glucose (FBG) and fasting insulin. Then, from the data We calculated it’s Homeostatic Model for Insulin Resistance (HOMA-IR) score to assess insulin sensitivity. Unpaired T test and chi-square were used to analyze the data. The study result showed the average levels of FBG and fasting insulin were lower in STH-infected group than STH-uninfected group. However, there was no significant difference between two groups (FBG p=0.678; fasting insulin p=0.075). Also, STH-infected group tend to had good insulin sensitivity (66.7%) than STH-uninfected group (45.8%), but statistically, there was no significant relationship between STH infection and insulin sensitivity with p value=0.244. In conclusion, there is no relationship between STH infection and insulin sensitivity. Keywords: Soil-transmitted Helminths, Insulin Sensitivity, FBG